Study protocol for a multiarm, randomized controlled trial to determine the effectiveness of community-based frailty rehabilitation to improve physical function in older adults: The OPTIMAL Fitness Trial - Alexandra Papaioannou; Courtney Kennedy; Justin Lee; Patricia Hewston; Caitlin McArthur; Shyam Maharaj; Jonathan Adachi; Pauline Boulos; Raja Bobba; Alexander Rabinovich; Brian McKenna; Lisa Palubiski; et al. (PLoS ONE, 2026)
Background Frailty in older adults is on the rise with the rapid aging population. Frailty is dynamic and proven to be reversible or treatable. Evidence regarding the clinical effectiveness of community-based frailty interventions is limited. Frailty rehabilitation has the potential to be an accessible community-based intervention that may enable independence. We will examine a model of frailty rehabilitation and consider key components for improving physical function, frailty, sarcopenia, and cost-effectiveness. Methods A multiarm, parallel-group, partially blinded, randomized controlled trial will compare the clinical and cost-effectiveness of OPTimizing Independence, Mobility, and Active Life (OPTIMAL) Fitness multimodal (group exercise, nutritional coaching/supplementation, medication optimization) versus OPTIMAL Fitness exercise-only and control. Participants in the OPTIMAL Fitness multimodal and exercise-only groups will attend exercise classes twice weekly for 4 months and be provided with a tailored one-hour home exercise program. We will recruit community-dwelling older adults living with frailty aged ≥65 years. Eligibility includes a FRAIL scale score of ≥2 (prefrail or frail), ability to ambulate 25 meters, follow two-step commands, and not attend another group exercise program. The target sample size is 324 participants (n = 108 per arm). The primary outcome is physical function measured via the Short Performance Physical Battery and the 400m Walk Test. Secondary outcomes include frailty change, sarcopenia, cognition, affect, quality of life, and healthcare utilization. Outcome analysis will be performed via generalized linear model analysis. Analyses will be based on the intention-to-treat principle. This protocol is guided by the Standard Protocol Items: Recommendations for Interventional Trials statement. Discussion This trial is the first to determine whether a community-based frailty rehabilitation intervention can improve physical function in older adults with frailty and the level of intervention needed. The results from the OPTIMAL Fitness study will guide the development of a standardized program that could be implemented in global regions. Trial registration ClinicalTrials.gov Identifier: NCT03824106 Registered January 31, 2019, https://www.clinicaltrials.gov/study/NCT03824106